An experimental investigation and modelling for travelling wire electrochemical machining of Monel 400 alloys. (11th April 2020) - Kalaimathi, M.; Venkatachalam, G.; Sivakumar, M.
Monel 400 alloys find its applications in aerospace and marine industries. It is tough to cut these alloys using conventional machine tools as the hardness is high and also these alloys work-harden during cutting. Travelling wire electrochemical machining (TWECM), can cut these alloys efficiently and improves material removal rate (MRR) and surface quality. In this investigation, an attempt was made to investigate the TWECM characteristics of Monel 400 alloys and model the equation for MRR with the three process parameters i.e. voltage (V), electrolyte concentration (EC) and travelling wire speed (TS). The response surface methodology (RSM) was employed for design and analysis of experiments. The contour plots were generated to understand the effect of machining parameters on MRR. Artificial neural networks (ANN) were implemented to predict the process parameters. The predicted values of MRR with regression equation and ANN are in close agreement with the experimental results.